TEACHER’S HUMOR USE IN THE CLASSROOM AND STUDENTS’ PERCEPTIONS OF ITS EFFECTIVENESS AND APPROPRIATENESS - Phạm, Thùy Linh (2020)
Humor has long been a naturally indispensable part of human life. It has existed and developed since the very first day of human history as Bill Kelly said ―After God created the world, He made man and woman. Then, to keep the whole thing from collapsing, He invented humor.‖ Humor is also considered an effective tool in every aspect; a sense of humor is ―part of the art of leadership, of getting along with people, of getting things done‖ (Dwight David Eisenhower, American 34th President). Education is certainly no exception. Research has shown a large number of benefits of humor as a pedagogical tool in the classroom. The class‘s atmosphere is more pleasant; students are more relaxed and feel at ease to participate. Particularly, there are possibly positive outcomes in their learning. For any teachers, especially the tired ones, humor is a useful prescription helping them, to be more comfortable and passionate in teaching. Humor makes them more approachable to their students.